2022
DOI: 10.3390/cancers14225706
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Lung Cancer Survival: An Updated Systematic Review and Meta-Analysis

Abstract: Introduction: The outbreak of COVID-19 poses an unprecedented challenge to global public health. Patients with cancer are at a higher risk during the SARS-CoV-2 pandemic. Patients with lung cancer and COVID-19 were compared to those without cancer and those with other malignancies for the main outcome of this study. The aim of this study was to evaluate the differences in susceptibility, disease severity, and mortality between lung cancer patients and the general population. Methods: Using PRISMA reporting gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…Recently, there is an association between lung cancer, COVID-19 and vaccines [ (Trivanovic et al, 2022), (Mao et al, 2021)]. Lung cancer patients have an increased risk from COVID-19 infection and exhibit poor outcomes [ (Oldani et al, 2022), (Aramini et al, 2022)]. In addition, genomics, transcriptomics, proteomics, lipidomics and metabolomics are important to be used to determine the mechanisms of disease development and carcinogenesis [ (Zhou et al, 2019;Zhang et al, 2020b;Boys et al, 2022)].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there is an association between lung cancer, COVID-19 and vaccines [ (Trivanovic et al, 2022), (Mao et al, 2021)]. Lung cancer patients have an increased risk from COVID-19 infection and exhibit poor outcomes [ (Oldani et al, 2022), (Aramini et al, 2022)]. In addition, genomics, transcriptomics, proteomics, lipidomics and metabolomics are important to be used to determine the mechanisms of disease development and carcinogenesis [ (Zhou et al, 2019;Zhang et al, 2020b;Boys et al, 2022)].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is one of the most threatening malignancies to population health, and its relevance began to be recognised after COVID-19 caused a public health emergency that swept the globe. Analysis data showed that patients with lung cancer had a poor prognosis, higher rates of death (HR = 2.00 [95% CI 1.52, 2.63], p < 0.01) and severe infection (HR = 1.47 [95%CI 1.06, 2.03], p = 0.02) compared to patients without cancer ( 110 ). As discussed here, the onset, progression, and prognosis of the two diseases are not isolated and may, in some cases, affect each other and are causal.…”
Section: Discussionmentioning
confidence: 99%
“…It is affected by the severity and the number of symptoms such as fatigue, loss of appetite, dyspnea, cough, pain, and blood in sputum, which are specific for lung tumors. [ 23 ] Considering the incurable nature of the disease, patients with lung cancer face many problems in all physical, mental, social, and spiritual dimensions and will have a very poor quality of life and physical performance. Therefore, in justifying this result, we can point to the different samples studied and the difficult treatment of lung cancer and its destructive and progressive effect on the quality of life of these patients.…”
Section: Discussionmentioning
confidence: 99%